Alternaria alternata Accelerates Loss of Alveolar Macrophages and Promotes Lethal Influenza A Infection - Caroline M. Percopo (Viruses, 2020)
Chronic inhalation of fungi and fungal components has been linked to the development of respiratory disorders, although their role with respect to the pathogenesis of acute respiratory virus infection remains unclear. Here, we evaluate inflammatory pathology induced by repetitive administration of a filtrate of the ubiquitous fungus, Alternaria alternata, and its impact on susceptibility to infection with influenza A. We showed previously that A. alternata at the nasal mucosae resulted in increased susceptibility to an otherwise sublethal inoculum of influenza A in wild-type mice. Here we demonstrate that A. alternata-induced potentiation of influenza A infection was not dependent on fungal serine protease or ribonuclease activity. Repetitive challenge with A. alternata prior to virus infection resulted proinflammatory cytokines, neutrophil recruitment, and loss of alveolar macrophages to a degree that substantially exceeded that observed in response to influenza A infection alone. Concomitant administration of immunomodulatory Lactobacillus plantarum, a strategy shown previously to limit virus-induced inflammation in the airways, blocked the exaggerated lethal response. These observations promote an improved understanding of severe influenza infection with potential clinical relevance for individuals subjected to continuous exposure to molds and fungi.